1998
DOI: 10.1046/j.1523-1755.1998.06718.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of renal function by prostaglandin E receptors

Abstract: Regulation of renal function by prostaglandin E receptors. Prostaglandin E 2 is the major cyclooxygenase product of arachidonic acid metabolism produced along the nephron. This autacoid interacts with four distinct, G-protein-coupled E-prostanoid receptors designated EP 1 -EP 4 . The intrarenal distribution of each receptor has been mapped and the consequences of receptor activation examined. EP 3 receptor mRNA is expressed highly in the medullary thick ascending limb (mTAL) and collecting duct (CD). EP 3 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
80
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 64 publications
6
80
0
Order By: Relevance
“…Although such a function in reproductive physiology has not previously been ascribed to these lipids, it is consistent with the diverse actions of PGs in numerous organ systems. For example, PGs have been shown to modify ion transport in a number of epithelia (27,28). It is possible that the ionic composition of the oviductal fluid is altered in the Ep2 -/-animals and that this, in turn, leads to reduced fertilization.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Although such a function in reproductive physiology has not previously been ascribed to these lipids, it is consistent with the diverse actions of PGs in numerous organ systems. For example, PGs have been shown to modify ion transport in a number of epithelia (27,28). It is possible that the ionic composition of the oviductal fluid is altered in the Ep2 -/-animals and that this, in turn, leads to reduced fertilization.…”
Section: Figurementioning
confidence: 99%
“…It is well established that PGs can stimulate renin release through actions on the juxtaglomerular apparatus; hormones that increase intracellular cAMP levels stimulate renin release by these specialized cells (35). Because 2 EP receptors, EP2 and EP4, are G s protein-coupled, it has been suggested that one or both of these receptors may mediate this action of PGE 2 (28,36).…”
Section: Figurementioning
confidence: 99%
“…Eicosanoids have been demonstrated to regulate the transepithelial NaCl transport in the mTAL (1,2,13,15,20). Moreover, a large body of evidence indicates that cytochrome P-450-dependent metabolites of arachidonic acid (AA) play an important role in regulating a variety of ion transporters in the kidney (8,23,27,29).…”
mentioning
confidence: 99%
“…Although studies with higher doses could help clarify this, indomethacin, nevertheless, has been shown to decrease urine output in conscious rats (13,18). This effect of indomethacin on urine flow has been attributed to its ability to inhibit prostaglandin synthesis, in particular prostaglandin E 2 (PGE 2 ), which inhibits vasopressin-stimulated water reabsorption in the collecting duct via EP3 receptor activation (19,20). Consequently there is increased tubular reabsorption of water resulting in decreased urine output.…”
Section: Discussionmentioning
confidence: 99%